ELECTRICITY CONSUMPTION: A CASE STUDY OF ENERGY EFFICIENCY PROGRAM AMONG KUIM (Journal of Engineering and Health Sciences, 2019)
Electricity is a key energy source and is essential for economic development in every country because all systems operating in the building are based on electrical power supply. However, what is more worrying now is the use of inefficient electricity can have a negative impact on the environment and humans. This paper aims to propose energy efficiency plans with technical and behavioral improvement measures for Islamic University College of Melaka (KUIM). Quantitative research designs have been developed for the analysis of electrical consumption records to identify trends and usage patterns. The energy efficiency plan contemplates short-term tangibles or intangible actions. It also considers the investment period and the repayment of significant steps. Reduction of energy consumption is expected if energy efficiency plans will be implemented. This paper emphasizes the importance of involving students, faculty and technical staff to work together in assessing the energy efficiency of the buildings they are studying and working.